Współpraca organizacji pozarządowych (NGO) z administracją publiczną – strategia i zasady: Cooperation of non governmental organizations (NGOs) with public administration – strategy and principles - Broniewska, Maria Janina (Management and Administration Journal, 2021)
The author of this article makes an attempt to analyze the nature and principles of cooperation between NGOs and public administration. The usefulness of this cross-sectoral model of cooperation was pointed out. It is important that both parties implement the strategy of cooperation and do not forget to follow the rules described in the model.